Monitorização terapêutica de fármacos utilizados no tratamento da tuberculose no Brasil - ALBERIO, Carlos Augusto Abreu (Universidade Federal do Pará, 2022)
Tuberculosis continues to be a public health problem throughout Brazil. Several efforts have been made to increase their cure rates, such as the use of the DOTS strategy (Directly Observed Treatment for Short Term) to reduce cases of abandonment and improve adherence to treatment. As a result of the increase in primary resistance to isoniazid, the Ministry of Health modified the therapeutic regimen in 2010, adjusting the doses of isoniazid and pyrazinamide, and adding ethambutol in the intensive treatment phase. Due to the lack of data on serum concentrations of first-line drugs in the brazilian population in this new scheme, this study aimed to determine the serum concentrations of rifampicin, isoniazid and pyrazinamide during treatment and its associations with hematological and biochemical alterations, adverse reactions and clinical outcomes. A prospective cohort study was carried out between september 2013 and november 2016 in two basic health units in the city of Belém (Pará). The most common adverse effects were gastric irritation and pruritus, especially in the intensive phase of treatment and the most frequent clinical outcome was discharge by cure (87.5%). There was a high rate of smear negative (98,90%) in the end of intensive treatment phase. Hematological parameters were determined by automatic cell counter (Cobas 2300®) and biochemical parameters by spectrophotometry (Varian®), which did not present any relevant changes during treatment. The drugs analyzed were rifampicin, isoniazid, and pyrazinamide, and their serum concentrations were determined by reverse phase high performance liquid chromatography (HPLC-RP). Rifampicin and isoniazid presented serum concentrations within the minimum inhibitory concentration (MIC), except for pyrazinamide, which presented values below MIC (3.3 μg/ml), but with a maximum concentration (Cmax) well above the recommended values (63.3 μg/ml). Female patients had higher serum rifampicin concentrations than males. The serum concentrations of rifampicin and isoniazid did not show significant variations between the intensive phase and the maintenance phase. The findings of this study allow us to conclude that the current treatment is safe and effective, since the minor adverse reactions were the most frequent, there were no relevant hematological and biochemical alterations, and the majority of the patients evolved to cure.